Controlled release of silibinin in GelMA hydrogels inhibits inflammation by inducing M2-type macrophage polarization and promotes vascularization in vitro. Issue 21 (3rd May 2022) - Xu, Weijian; Sun, Yingjia; Wang, Jia; Wang, Baixiang; Xu, Fanxing; Xie, Zhijian; Wang, Yu
Abstract : This study suggests that Sil-GelMA hydrogels have an anti-inflammatory effect and the potential to promote vascularization. These Sil-GelMA hydrogels might provide a promising prospect for prevention of dry sockets in the future. Abstract : A dry socket is one of the most common complications after tooth extraction. The main etiologies are the loss of blood clots in the socket and the inflammation reaction caused by infection. Current studies on how to prevent dry sockets could not solve these two etiologies at the same time. Recent studies have demonstrated the anti-inflammation role of silibinin. In this study, silibinin was engineered into GelMA hydrogels (Sil-GelMA) with a concentration of 30 mM. The surface characteristics were observed by scanning electron microscopy and the successful loading of silibinin was detected by FTIR spectrometry. The Sil-GelMA hydrogels presented the sustained release ability of silibinin and slow degradation performance of GelMA. Furthermore, silibinin inhibited the inflammatory reaction by inducing M2-type macrophage polarization, promoting the secretion of anti-inflammatory factors (CD206, IL-10) and inhibiting the secretion of anti-inflammatory factors (IL-1β, iNOS). Silibinin also increased the secretion of vascularization-related factor VEGF and promoted vascularization in vitro . This study suggested that the Sil-GelMA hydrogels not only had an anti-inflammatory effect, but also had the potential to promote vascularization. Based on these results, the Sil-GelMA hydrogels might provide a promising prospect for prevention of dry sockets in the future.